2015
DOI: 10.5713/ajas.15.0587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fecal Microbiota of Mongolian and Thoroughbred Horses by High-throughput Sequencing of the V4 Region of the 16S rRNA Gene

Abstract: The hindgut of horses is an anaerobic fermentative chamber for a complex and dynamic microbial population, which plays a critical role in health and energy requirements. Research on the gut microbiota of Mongolian horses has not been reported until now as far as we know. Mongolian horse is a major local breed in China. We performed high-throughput sequencing of the 16S rRNA genes V4 hypervariable regions from gut fecal material to characterize the gut microbiota of Mongolian horses and compare them to the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 26 publications
6
63
0
Order By: Relevance
“…As mentioned above, Firmicutes and Bacteroidetes were the dominant bacteria at a ratio of 1:1 in the LG of the horses, the result contradicted the observations using fecal samples (Costa et al, 2012; Costa, Stampfli, et al, 2015; Schoster, Mosing, Jalali, Staempfli, & Weese, 2016; Zhao et al, 2016). However, this result is consistent with studies on microbial communities in different parts of the intestine (Costa, Silva, et al, 2015; Ericsson, Johnson, Lopes, Perry, & Lanter, 2016).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…As mentioned above, Firmicutes and Bacteroidetes were the dominant bacteria at a ratio of 1:1 in the LG of the horses, the result contradicted the observations using fecal samples (Costa et al, 2012; Costa, Stampfli, et al, 2015; Schoster, Mosing, Jalali, Staempfli, & Weese, 2016; Zhao et al, 2016). However, this result is consistent with studies on microbial communities in different parts of the intestine (Costa, Silva, et al, 2015; Ericsson, Johnson, Lopes, Perry, & Lanter, 2016).…”
Section: Discussionmentioning
confidence: 75%
“…This bacterium is an appealing candidate to become a human probiotic because of negative correlation with the incidence of obesity, diabetes, inflammation, and metabolic disorders (Everard et al, 2013; Hansen et al, 2012; Png et al, 2010; Wang, Bose, Kim, Han, & Kim, 2015). Only four previous studies (Costa, Stampfli, Allen‐Vercoe, & Weese, 2016; Costa, Stampfli, et al, 2015; Rodriguez et al, 2015; Zhao et al, 2016) described the genus Akkermansia in the equine intestinal microbiota, which was only found in stool samples. In this study, for the first time, we found the ventral colon had the highest content of Akkermansia in the gastrointestinal tract of Mongolian horses, which supports further study of this bacterium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that there may be two main reasons for this phenomenon, one is that soft feces is rich in vitamins and microbial proteins, with the same feed intake, rabbits that were fasted to eating feces would consume 15% to 22% less protein. The other one reason is that soft feces of rabbits contain a large number of microorganisms, when forbid the rabbits from eating soft feces, resulting in changes in the microflora in their digestive tract and the reduction of bacterial populations [38, 39].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have employed many methods for DNA extraction from equine fecal samples, which has been predominantly used to analyse the equine hind gut microbial profile. Although most of the studies have used fecal DNA kits [5][6] , many have also used soil microbe DNA kits [7][8] or total DNA isolation kits 9 . The DNA extraction method is a critical step in microbial community profiling as apart from its effect on sequencing output and microbial community profiling 10 , it adversely affects the result comparison across studies, especially in physiological and pathological studies [11][12] .…”
Section: Introductionmentioning
confidence: 99%